2009
DOI: 10.1063/1.3064159
|View full text |Cite
|
Sign up to set email alerts
|

Self-pulsing 104 A cm−2 current density discharges in dielectric barrier Al/Al2O3 microplasma devices

Abstract: Excitation of Al/Al2O3 microplasma devices with 50 μs, 800 V pulses produces, in Ar/H2 gas mixtures at 600 Torr, ∼6 A current pulses with a duration of ∼30 ns. Corresponding to peak current and power densities of ∼104 A/cm2 and ∼2.5 GW/cm3, respectively, these pulses are generated in a 10 μs burst in which the voltage self-pulses at a repetition frequency of ∼3 MHz. Analysis of the Hα, Hβ, and Ar II emission line profiles yields a plasma density of ∼1017 cm−3, and the emission of O IV ions suggests the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Consequently, the cathode fall potential in the gas phase plasma is also electronically controllable. [12]. Thus, in surveying the landscape of e − -h + and e − -ion (gas phase) plasma characteristics, one cannot avoid the conclusion that not only are the two related from a general, philosophical perspective, but any distinctions between them with regard to physical parameters are vanishing rapidly.…”
Section: The Recent Realization Of Optoelectronic Devices Based On Inmentioning
confidence: 94%
“…Consequently, the cathode fall potential in the gas phase plasma is also electronically controllable. [12]. Thus, in surveying the landscape of e − -h + and e − -ion (gas phase) plasma characteristics, one cannot avoid the conclusion that not only are the two related from a general, philosophical perspective, but any distinctions between them with regard to physical parameters are vanishing rapidly.…”
Section: The Recent Realization Of Optoelectronic Devices Based On Inmentioning
confidence: 94%
“…Indeed, experiments of the past two decades have demonstrated that, depending upon the microcavity design, fill gas mixture and pressure, and driving voltage, steady-state n e values of 10 12 -10 15 cm −3 are obtained routinely in CW microplasmas. Pulsed excitation has extended the range in peak electron densities in rare gas plasmas from 10 16 to >10 17 cm −3 [33], and figure 4 shows that such values for the electron number density place microcavity plasmas in uncharted territory. Prepared by Prof. Tachibana [34], this figure is a map of a portion of plasma parameter space in which the characteristic dimension of the plasma (d), shown by the abscissa, ranges from 100 mm to 10 −5 mm.…”
Section: Overview Of Microplasma Physics and Characteristicsmentioning
confidence: 99%
“…Confining low-temperature plasma to cavities having a characteristic dimension d below 1 mm was quickly found to yield plasmas capable of operating continuously at atmospheric pressure, and yet efficiently populating highly excited states of both neutral and ionic species. [1][2][3][4][5] Not only have peak electron densities (n e ) >10 17 cm −3 been reported, [6] but the close association between n e and the local values of E/N and T e results in plasmas in which E (magnitude of the electric field) and E/N frequently exceed 10 4 V/cm and 10 −15 V-cm 2 (100 Td), respectively. [5,7] The former of these (1 V/μm) is near or above the threshold for Fowler-Nordheim electron emission from nanostructures located on the cavity wall, thereby allowing for the injection of electrons into the plasma sheath.…”
Section: Introductionmentioning
confidence: 99%